Effect of surface sealants on color stability of different resin composites - KORKUT, BORA (My University, 2022)
Objective. The aim was to assess the effect of surface sealants on the color stability of different composite materials. Methodology. 120 samples were prepared using Filtek Ultimate (3M, USA), Charisma Topaz (Kulzer, Germany), and Clearfil Majesty Es-2 Premium (Kuraray Noritake, Japan) composites. The samples were polished with polishing discs and divided by test groups (n=10 for each), regarding the sealant used; Permaseal (Ultradent Products, USA), Biscover LV (Bisco, USA), Optiglaze Clear (GC Corp., Japan) and control. The samples were discolored for 144 hours in coffee solution at constant 37ºC, renewing daily. Color measurements were performed at the baseline, following the sealant application, and after discoloration procedure, using a spectrophotometer (EasyShade 5, Vita-Zahnfabrik, Germany). The collected L*C*h* coordinates were converted to corresponding L*a*b* coordinates and the color changes (∆E) were calculated. Results. All the sealants presented perceptible (>1.2) and unacceptable (>2.7) color changes. Biscover LV presented the lowest ∆E among all sealants (p<0.001). The highest ∆E was observed for Permaseal (p<0.001). Color changes for Optiglaze and control groups were similar (p≥0.05). Filtek Ultimate presented the highest color stability (p<0.001), followed by Charisma Topaz and Clearfil Majesty. The combination of Filtek Ultimate with Biscover LV was considered to have the highest color stability, whereas the combination of Clearfil Majesty with Permaseal was considered the lowest, among all. Conclusion. Experimented sealants were considered relatively effective on color stability of resin composites depending on the type of the sealant and the composite material. However, the use of surface sealants may not be advantageous every time. Biscover LV have inhibited the level of discoloration, whereas Permaseal had an increasing effect generally
Keywords: sealant; Biscover LV; Optiglaze; Permaseal; discoloration; surface staining